SMART TECHNOLOGIES IN THE VISUAL LITERACY DEVELOPMENT - Riznyk, Viacheslav; Ostroha, Mariia; Bespalyi, Vladyslav (Physical and Mathematical Education, 2025)
Formulation of the problem. The emergence of digital technologies has revolutionized education by placing a significant emphasis on visual learning and communication, which today is based on flexible, personalized, and technologically rich learning environments with a variety of multimedia content, digital visualizations, virtual simulations, etc. The purpose of the article: to study the use of SMART technologies for the development of visual literacy Materials and methods: analysis of scientific literature to clarify the essence of the concepts of "visual literacy", "SMART-technologies" and their components, to study current trends and approaches to the implementation of visual learning; systematization and generalization to structure the impact of SMART-technologies on visual literacy, to identify SMART-tools in the context of visual learning; comparative analysis to compare traditional and SMART-oriented approaches to the development of visual literacy, to study foreign and domestic experience in the implementation of visual learning. Results. It is substantiated that the theoretical basis for the use of SMART technologies in the development of visual literacy is the cognitive theory of multimedia learning, the theory of double coding, constructivist and socio-cognitive theories, which emphasize the importance of active participation of students in the creation and interpretation of visual content. It is proven that SMART technologies cover a wide range of digital tools and platforms that can be used to improve visual literacy: interactive whiteboards, virtual and augmented reality, multimedia creation tools, and data visualization software Conclusion. The integration of SMART technologies creates conditions for personalized and creative learning based on the active use of visual content. The effectiveness of such approaches is determined by the digital and pedagogical competence of teachers, the availability of technology, and the ability of students to critically evaluate visual information. Further development is directly linked to the introduction of artificial intelligence and immersive technologies that expand the possibilities for the development of visual literacy in the context of the digital transformation of education.